2009
DOI: 10.1507/endocrj.k08e-311
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH) or Insulin-like Growth Factor (IGF)-I Represses 11.BETA.-Hydroxysteroid Dehydrogenase Type 1 (HSD1) mRNA Expression in 3T3-L1 Cells and Its Activity in Their Homogenates

Abstract: Abstract.Patients with growth hormone (GH) deficiency (GHD) have a clinical feature of visceral adiposity and it has been reported that these patients have an increased active cortisol (F)/inactive cortisone (E) metabolite ratio. 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is an enzyme expressed in liver and adipose tissue that acts principally as a reductase converting E to F. In the present study, we investigated the effects of GH or IGF-I on the activity of 11β-HSD1 in 3T3-L1 cell homogenates and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Due to these increased levels, we decided to use fully differentiated adipocytes on the tenth day after induction of differentiation for our experiments. Levels of 11β-HSD1 mRNA were decreased by GH and IGF-I in these fully differentiated adipocytes as we previously reported [8]. The repression of 11β-HSD1 mRNA by IGF-I treatment was partially restored by linsitinib.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Due to these increased levels, we decided to use fully differentiated adipocytes on the tenth day after induction of differentiation for our experiments. Levels of 11β-HSD1 mRNA were decreased by GH and IGF-I in these fully differentiated adipocytes as we previously reported [8]. The repression of 11β-HSD1 mRNA by IGF-I treatment was partially restored by linsitinib.…”
Section: Discussionsupporting
confidence: 87%
“…Our previous study also indicated that 11β-HSD1 activity and messenger ribonucleic acid (mRNA) expression were suppressed by both GH and insulin-like growth factor (IGF)-I in 3T3-L1 adipocytes [8]. These findings suggest that lack of GH and IGF-I may cause activation of 11β-HSD1 in patients with adult GH deficiency, and induce metabolic disorders related to insulin resistance.…”
Section: Measurement Of 11β-hsd1 H6pdh and Igf-i Mrnamentioning
confidence: 86%
See 1 more Smart Citation
“…As energy-source materials, free fatty acids (FFAs) and glucose are important in obesity and obesity-related insulin sensitivity. Furthermore, studies have indicated that glucocorticoids and growth hormone (GH) are also closely associated with obesity and insulin resistance (6,7). However, the molecular mechanisms underlying the effects of FFAs, glucose, glucocorticoids and GH in obesity and insulin sensitivity, have not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that GH down-regulates 11βHSD1 (11β-hydroxysteroid dehydrogenase type 1) expression in the adipose tissue (Morita et al, 2009; Zhao et al, 2011). 11βHSD1 amplifies glucocorticoid action by stimulating the conversion of inactive dehydrocorticosterone to active corticosterone.…”
Section: Introductionmentioning
confidence: 99%